Developing transferable skills through engagement with higher education laptop ensembles. Issue 1 (22nd May 2012) - Mudd, Tom
This article argues that ensemble playing forms the backbone of transferable skills development in higher education music courses, and demonstrates how laptop ensembles, as well as being musically engaging projects in their own right, can be a useful way of integrating such skill development into more technologically oriented music degrees. The fact that such ensembles have few established modes of practice allows them to be particularly open to student engagement in a variety of roles and can help to promote an active learning environment. Approaches to structuring the organization of such an ensemble to promote these pedagogical aspects are discussed and related to the four stages laid out by David Kolb's experiential learning model.